Model pemeriksaan kesehatan berdasarkan komposisi tubuh terhadap peningkatan aktifitas fisik dan kualitas hidup lanjut usia - Ichsan Ichsan; Alfridsyah Alfridsyah (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Quality of Life is an assessment of the quality of life based on four domains, namely physical health, psychological conditions, social relationships, and the environment. The Healthy Living Community Movement (called GERMAS) focuses on physical activity, and regular health checks to improve quality of life, increase productivity, and lower health care costs.Objective: This study aims to see how effective the body composition health examination model is at increasing physical activity and quality of life in the elderly.Method: This quantitative research design is a quasi-experimental study conducted in Ulee Kareng District, Banda Aceh, in 2018. The sample, namely the elderly, was taken non-randomly, as many as 54 people. Data was collected by means of interviews and anthropometric measurements. The data is processed through the stages of editing, coding, tabulating, and cleaning. The analysis used a statistical with dependent t-test at 95% CI.Results: There is a difference in domain I (first), namely the physical health of the elderly, between the results of the pre-test (63.6 ± 15.248) and the results of the post-test (65.7 ± 14.872) with a p-value = 0.021 (p < 0.05). On the other hand, in domains II, III, and IV, there was no difference in the physical health of the elderly before and after the measurement (p > 0.05).Conclusion: Health examination through measuring body fitness affects the physical health of the elderly in domain I (first) but does not affect domains II, III, and IV.